Ceftriaxone prevents the induction of cocaine sensitization and produces enduring attenuation of cue- and cocaine-primed reinstatement of cocaine-seeking - Sondheimer, Ilan (2011)
Ceftriaxone is a beta-lactam antibiotic which has been found to increase the expression and function of the major glutamate transporter, GLT-1. It has previously been shown that GLT-1 expression is decreased in the nucleus accumbens following cocaine self-administration and extinction training; ceftriaxone given in the days immediately prior to reinstatement testing attenuates both cue- and cocaine-primed reinstatement. Here we tested the ability of ceftriaxone pre-treatment (for 5 days prior to the first cocaine exposure) to prevent the induction of cocaine sensitization and the acquisition of cocaine self-administration. We also tested whether ceftriaxone administered only during self-administration attenuates the reinstatement of extinguished cocaine-seeking. We found that ceftriaxone did not affect the acquisition of cocaine self-administration but was able to attenuate reinstatement weeks after ceftriaxone administration ceased. This attenuation in reinstatement was accompanied by a restoration of GLT-1 expression in the nucleus accumbens. Ceftriaxone also attenuated locomotor behavior following the first cocaine injection and prevented the induction of cocaine but not caffeine sensitization. While ceftriaxone-treated animals did not sensitize to caffeine, they displayed reduced caffeine-induced locomotion following repeated caffeine treatment, indicating a possible dopaminergic effect of ceftriaxone. Taken together, these results indicate that ceftriaxone produces enduring changes in glutamate homeostasis in the nucleus accumbens which counteract addiction-related behaviors.